2006
DOI: 10.1007/s10470-006-8119-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, testing and optimisation of electrostatic comb-drive levitational actuators

Abstract: This work presents an analysis of the levitation effect in electrostatic comb fingers and of its possible use for vertical or torsional actuation of micromachined structures. Two different levitational mechanical resonators were designed and fabricated in a thick-polysilicon technology. A study of the dependence of the force intensity on the geometric parameters of the actuators were performed using FEM simulations, and information about critical geometrical parameters in the design of operative levitational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…They found that the effect can be predicted and, in some cases, counteracted by a special design. A more comprehensive finite element modeling (FEM) of the levitation effect has been performed more recently [4][5][6]. The effect can also be put to use, as shown in [7], where it is used for vertical actuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the effect can be predicted and, in some cases, counteracted by a special design. A more comprehensive finite element modeling (FEM) of the levitation effect has been performed more recently [4][5][6]. The effect can also be put to use, as shown in [7], where it is used for vertical actuation.…”
Section: Introductionmentioning
confidence: 99%
“…The fringe field lines from the top cause a net force upward. simulation studies[4][5][6] do not contain an investigation of the total comb drive capacitance change as a function of the applied driving voltage, but only as a function of the change in the height of the comb drive. Therefore, it is difficult to directly use the results from these studies for correcting the capacitance change like the one given in figure 3 for the levitation effect.…”
mentioning
confidence: 99%
“…Levitation modelling by used object-oriented methods Subject of calculations of the levitation forces and balance point in comb structures was taken up frequently. The analytical calculations based on the circuit modelling of capacitances were presented by van Spengen ( 2007) and Molfese et al (2006). The another methods were presented in Liao et al (2004) and Chyuan et al (2005).…”
Section: Numerical Modeling Of 3-d Comb Drivementioning
confidence: 99%
“…[1,5]. Apart from this typical parallel plate actuation configuration, other different ways to apply the electrostatic force have been developed by different groups [3,4,7] for in-plane and out-of-plane actuation.…”
Section: Introductionmentioning
confidence: 99%
“…A way to increase the force and, therefore, displacement for in-plane working devices is based on the array of comb-finger actuators [3]. Usually, these devices require a large area.…”
Section: Introductionmentioning
confidence: 99%